APPLICATION OF THE METAPHOR APPROACH IN GERMAN LEARNING AT SMA NEGERI 7 AMBON - Patresia S Apituley; Carolina Lestuny; Piet Soumokil (JURNAL TAHURI, 2022)
The purpose of this study 1) To determine the impact of applying metaphors on learning German. 2) To Improve and optimize the role of the teacher's metaphor in learning German. The population in this study were all students of SMA Negeri 7 Ambon, while the selected samples were students grade 10 of SMA Negeri 7 Ambon. The results of the dependent t-test calculation showed that the t-value is more than the t-table (t-value 11.30 > t-table 1.72913). The results of these calculations indicated that there was a significant difference between German learning’s outcomes before and after treatment with the application of metaphors. Thus, it can be said that application of metaphor had a positive impact and can effectively assist students in learning German and increase learning outcomes of students